2018
DOI: 10.1080/10749357.2018.1493072
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative study exploring views and experiences of people with stroke undergoing transcranial direct current stimulation and upper limb robot therapy

Abstract: Background: Neurorehabilitation technologies used mainly in research such as robot therapy (RT) and transcranial direct current stimulation (tDCS) can promote upper limb motor recovery after stroke. Understanding the feasibility and efficacy of stroke rehabilitation technologies for upper limb impairments is crucial for effective implementation in practice. Small studies have explored views of RT by people with stroke; however experiences of people receiving tDCS in combination with RT have never been explored… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
42
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(49 citation statements)
references
References 32 publications
3
42
4
Order By: Relevance
“…activity and participation). These outcomes are contrary to the only (known) previous qualitative study in the eld of non-invasive brain stimulation of Triccas et al (2018) (14), where patients felt that receiving tDCS and robotic therapy was especially effective for their strength and tightness in the affected upper limb. This discrepancy in results could be explained by the design of the studies.…”
Section: Bene Ts and Concerns Related To Rtms Treatmentcontrasting
confidence: 99%
See 3 more Smart Citations
“…activity and participation). These outcomes are contrary to the only (known) previous qualitative study in the eld of non-invasive brain stimulation of Triccas et al (2018) (14), where patients felt that receiving tDCS and robotic therapy was especially effective for their strength and tightness in the affected upper limb. This discrepancy in results could be explained by the design of the studies.…”
Section: Bene Ts and Concerns Related To Rtms Treatmentcontrasting
confidence: 99%
“…One of the main concerns were feelings of anxiety about the 'electricity' within the brain and uncertainty about possible negative consequences. This nding is consistent with ndings from Triccas et al (2018) (14) who reported that patients undergoing tDCS treatment had concerns about the 'electricity' applied via the electrodes, and were insecure about possible negative consequences. Some patients found the stimulation pulses annoying.…”
Section: Bene Ts and Concerns Related To Rtms Treatmentsupporting
confidence: 91%
See 2 more Smart Citations
“…This confirms the good tolerance for this type of treatment. An interview study that explored the views and experiences of 21 patients who underwent tDCS combined with robotic therapy for upper limp recovery, revealed that the therapy was generally experienced as effective and comfortable [ 14 ]. However, some patients also reported discomfort (e.g.…”
Section: Introductionmentioning
confidence: 99%